Regression Analysis of Phenotypic Traits of West African Dwarf Goats (Capra Hircus) In Derived Savanna Zone of Nigeria - Tella, Adetunmbi (Universitas Islam Negeri Alauddin Makassar, 2025)
Three hundred and ninety-nine (399) West African dwarf goats from the Ejigbo Local Government Area in Osun State and the surrounding Derived Savanna Zone of Nigeria were evaluated for body measures and live weight. Analysis was done on data pertaining to 194 bucks and 205 does. These were categorized into six age groups (milk teeth, 2-teeth, 4-teeth, 6-teeth, 8-teeth, and worn teeth) and recorded by sex. The purpose of the study was to characterize the phenotype of the WAD goat and identify the best model or models for predicting liveweight based on body measures in the experimental location, which is Nigeria's derived savanna zone. For both sexes, body measurement values rose significantly (P < 0.05) with age. In bucks, the average body weight was 5.32 ±0.15 to 29.63±1.88 kg, while in does, it was 5.75±0.13 to 30.29±1.22 kg. In terms of body weight and other physical parameters, sex variations were discovered. For quantitative features including heart circumference, body length, rump height, foreleg height, and withers height, the fitted linear regression equations also show that the coefficients were positive and significant (P < 0.05). Moreover, at all ages, multiple regression considerably increased the coefficient of determination (R2) (P < 0.05). In summary, body weight and linear body measurements are economically significant characteristics in animal genetic resources, particularly for small ruminants like goats during selection, to offer precise weight determination in isolated locations without a scale.